Paired Associative Stimulation of the Temporal Cortex: Effects on the Auditory Steady-State Response - Engel, Sarah; Markewitz, Robert Daniel Heinrich; Langguth, Berthold; Schecklmann, Martin (Frontiers in Psychiatry, 2017)
Background: Paired associative stimulation (PAS) is the repeated combination of a sensory stimulus with transcranial magnetic stimulation (TMS) in close temporal association. Recently, a study demonstrated that PAS of an auditory stimulus together with TMS of the temporal cortex is capable of changing the amplitude of auditory evoked potentials (AEPs). Objective: This study examined the influence of tone duration and habituation in temporal cortex PAS as elicited by 40 and 20 Hz amplitude modulated (AM) auditory steady state responses (aSSR). Methods: Eighteen subjects participated in two experiments, including two PAS protocols each, which consisted of 200 auditory stimuli (4 kHz) paired with temporal cortex TMS with an interstimulus interval (ISI) of 45 ms between tone onset and TMS-pulse, delivered at 0.1 Hz. Experiment 1 compared auditory stimuli with different lengths (PAS (23 ms) vs. PAS (400 ms)). Experiment 2 investigated verum vs. sham PAS. aSSRs for the paired tone (4 kHz) and a control tone (1 kHz) were measured pre- and post-interventional - using 40 Hz aSSR in experiment 1 and both 20 and 40 Hz aSSR in experiment 2. Results: A statistically significant, sham-controlled decrease in amplitude was observed for the 20 Hz aSSR using the 4 kHz PAS carrier frequency in experiment 2. Conclusion: Frequency specific effects for the 20 Hz aSSR confirm the feasibility of auditory PAS and highlight the secondary auditory cortex as its target site, introducing new possible treatment protocols for patients suffering from tinnitus. The amplitude decrease can be explained by principles of spike-timing dependent plasticity (STDP) and the superposition model of aSSR.